Cyclooxygenase-2 prostaglandins mediate anandamide-inhibitory action on nitric oxide synthase activity in the receptive rat uterus - Sordelli, Micaela Soledad (2012)
Anandamide, an endocannabinoid, prostaglandins derived from cyclooxygenase-2 and nitric oxide synthesized by nitric oxide synthase (NOS), are relevant mediators of embryo implantation. We adopted a pharmacological approach to investigate if anandamide modulated NOS activity in the receptive rat uterus and if prostaglandins mediated this effect. As we were interested in studying the changes that occur at the maternal side of the fetalmaternal interface, we worked with uteri obtained from pseudopregnant rats. Females were sacrificed on day 5 of pseudopregnancy, the day in which implantation would occur, and the uterus was obtained. Anandamide (2 ng/kg, i.p.) inhibited NOS activity (P < 0.001) and increased the levels of prostaglandin E2 (P < 0.01) and prostaglandin F2α(P < 0.01). These effects were mediated via cannabinoid receptor type 2, as the pre-treatment with SR144528 (10 mg/kg, i.p.), a selective cannabinoid receptor type 2 antagonist, completely reverted anandamide effect on NOS activity and prostaglandin levels. The pre-treatment with a non-selective cyclooxygenase inhibitor (indomethacin 2.5 mg/kg, i.p.) or with selective cyclooxygenase-2 inhibitors (meloxicam 4 mg/kg, celecoxib 3 mg/kg, i.p.) reverted anandamide inhibition on NOS, suggesting that prostaglandins are derived from cyclooxygenase-2 mediated anandamide effect. Thus, anandamide levels seemed to modulate NOS activity, fundamental for implantation, via cannabinoid receptor type 2 receptors, in the receptive uterus. This modulation depends on the production of cyclooxygenase-2 derivatives. These data establish cannabinoid receptors and cyclooxygenase enzymes as an interesting target for the treatment of implantation deficiencies. © 2012 Elsevier B.V. All rights reserved.